2022
DOI: 10.1007/s00264-022-05338-9
|View full text |Cite
|
Sign up to set email alerts
|

Tenodesis yields better functional results than tenotomy in long head of the biceps tendon operations—a systematic review and meta-analysis

Abstract: Background Pathology of the long head of the biceps tendon (LHBT) is a common disorder affecting muscle function and causing considerable pain for the patient. The literature on the two surgical treatment methods (tenotomy and tenodesis) is controversial; therefore, our aim was to compare the results of these interventions. Methods We performed a meta-analysis using the following strategy: (P) patients with LHBT pathology, (I) tenodesis, (C) tenotomy, (O) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 64 publications
(202 reference statements)
0
6
0
Order By: Relevance
“…The advantages of this technique are simple operation, excellent visualization, and easy to be taught and repeated under arthroscopy. At the same time, it is a cost-effective technology, because: (1) It is a simple and timeconsuming technology, which saves operation time; (2) The two suture limbs can be pressed under the lateral row handling the rotator cuff without additional implants, which The following limitations of our study must be considered. First, this tenodesis technique has potential limitations similar to those of other all-arthroscopic tenodesis techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of this technique are simple operation, excellent visualization, and easy to be taught and repeated under arthroscopy. At the same time, it is a cost-effective technology, because: (1) It is a simple and timeconsuming technology, which saves operation time; (2) The two suture limbs can be pressed under the lateral row handling the rotator cuff without additional implants, which The following limitations of our study must be considered. First, this tenodesis technique has potential limitations similar to those of other all-arthroscopic tenodesis techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions of the long head of the biceps tendon (LHBT) usually lead to pain of the shoulder and disability, and more than 60% of patients have a rotator cuff tear ( 1 ). Tenotomy and tenodesis are effective but controversial techniques for the treatment of LHBT lesions; however, there was no difference in functional results between tenotomy and tenodesis in recent studies ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tendinopathy of the long head of the biceps tendon (LHBT), which occurs in isolation or is accompanied by other shoulder pathologies, is a common cause of anterior shoulder pain [ 2 , 28 ]. Surgical interventions for LHBT tendinopathy include tenotomy and tenodesis [ 13 , 21 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tendinopathy of the long head of the biceps tendon (LHBT), which occurs in isolation or is accompanied by other shoulder pathologies, is a common cause of anterior shoulder pain [ 2 , 28 ]. Surgical interventions for LHBT tendinopathy include tenotomy and tenodesis [ 13 , 21 , 28 ]. Although both tenotomy and tenodesis lead to comparable clinical outcomes [ 1 , 21 , 22 , 24 ], there is a trend that patients prefer tenodesis to tenotomy owing to concerns regarding Popeye deformity [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies previously identified LHBT injury as a cause of shoulder pain, either in isolation or in conjunction with other shoulder pathologies. 1 …”
mentioning
confidence: 99%